Strategies to reduce plate waste in primary schools – experimental evaluation. Issue 8 (28th October 2015) - Liz Martins, Margarida; Rodrigues, Sara SP; Cunha, Luís M; Rocha, Ada
Abstract: Objective: To determine and compare the effect of two interventions in reducing the plate waste of school lunches. Design: A between-group analysis was conducted among children from three primary schools: (i) a group receiving intervention A, designed for children and focusing on nutrition education and food waste; (ii) a group receiving intervention B, intended for teachers and focusing on the causes and consequences of food waste; and (iii) a control group with no intervention. For each child, physical weighing of individual meals and leftovers was performed on three non-consecutive weeks at baseline (T0), 1 week (T1, short term) and 3 months (T2, medium term) following the intervention. Plate waste was recorded for a total of 1742 lunches during 14 d over eight different menus. Setting: Portuguese public primary schools in the city of Porto. Subjects: All fourth-grade children ( n 212) attending the three preselected schools. Results: After intervention A focusing on nutrition education designed for children, a decrease in soup waste was observed compared with the control group. The effect was greater at T1 (−11·9 (se 2·8) %; P <0·001) than at T2 (−5·8 (se 4·4) %; P =0·103). The plate waste of identical main dishes decreased strongly at T1 (−33·9 (se 4·8) %; P <0·001). However, this effect was not found at T2 (−13·7 (se 3·2) %; P <0·001). After intervention B involving teachers, plate waste decreased at T2 (−5·5 (se 1·9) % for soup; −5·4 (se 2·4) % for identical main dishes). Conclusions: Nutrition education designed for children was more effective in the short than the medium term. Thus, this kind of intervention was not effective in reducing food waste in the medium term. In contrast, an intervention focusing on teachers revealed better results in the medium term than in the short term.